Kearifan Lokal dalam Tradisi Metri sebagai Materi Budaya dalam Pembelajaran Bahasa Indonesia bagi Penutur Asing - Mulyaningtyas, Rahmawati; Arinugroho, Yogi Dian (Universitas Muhammadiyah Jember, 2025)
The metri tradition embodies the local wisdom of the community, both in the dishes served and the prayers spoken by the leader of the metri. The local wisdom in the metri tradition can be utilized as cultural material for BIPA (Bahasa Indonesia untuk Penutur Asing: Indonesian Language for Foreigner) learners. Cultural material in BIPA learning plays an important role in teaching language. By introducing the traditions or cultures of the community, learners will have an easier time understanding the meaning of the language they are learning. Learning through culture will be more engaging and memorable for foreign learners. This research is a descriptive qualitative research. This is because the research focuses on the traditions in the community as cultural material in BIPA learning. The data sources for this research are four people: three metri leaders and one resident of Ringinpitu who still preserves the metri tradition. Data were obtained from interviews and documentation of recordings during the implementation of the metri tradition. The research findings show that the local wisdom in the metri tradition can be viewed from the implementation of the metri event, the dishes served, and the prayers spoken by the leader of the metri.